Cosmological Constraints from Multiple Probes in the Dark Energy Survey - Abbott, T. M.C.; Alarcon, A.; Allam, S.; Andersen, P.; Andrade-Oliveira, F. [UNESP]; Annis, J.; Asorey, J.; Avila, S.; Bacon, D.; Banik, N.; Bassett, B. A.; Baxter, E.; et al. (American Physical Society (APS), 2019)
The combination of multiple observational probes has long been advocated as a powerful technique to constrain cosmological parameters, in particular dark energy. The Dark Energy Survey has measured 207 spectroscopically confirmed type Ia supernova light curves, the baryon acoustic oscillation feature, weak gravitational lensing, and galaxy clustering. Here we present combined results from these probes, deriving constraints on the equation of state, w, of dark energy and its energy density in the Universe. Independently of other experiments, such as those that measure the cosmic microwave background, the probes from this single photometric survey rule out a Universe with no dark energy, finding w=-0.80-0.11+0.09. The geometry is shown to be consistent with a spatially flat Universe, and we obtain a constraint on the baryon density of ωb=0.069-0.012+0.009 that is independent of early Universe measurements. These results demonstrate the potential power of large multiprobe photometric surveys and pave the way for order of magnitude advances in our constraints on properties of dark energy and cosmology over the next decade.